Espectro trófico de peces concurrentes al área de crianza Playa Chipana (21° 19'S -7000 W )del norte de Chile - Vargas F., Mauricio (Universidad de Costa Rica, 1999)
A total of 361 fishes incluiding Odonthestes regia. Paralabax humeralis Isacia conceptions, Cilus gilbeti Menticirrhus ophicephalus, Sciaena deliciosa and Scomber japonicus were colleted in the nursery area Plata Chiapa (21°19 S)